Maryna Delyusto: PHRASEOLOGY OF THE UKRAINIAN DIALECTS SPREAD BETWEEN THE DNIESTER AND THE DANUBE RIVERS - Delyusto, Maryna (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
Аbstract. Introduction. The information about the phraseological level of the Ukrainian resettlement dialects spread in the area between the Dniester and the Danube rivers is still fragmentary and insufficiently systematized, in particular regarding their areal relevance. In our opinion, dialectal   phenomena of phraseological level are very important for establishing the origin and dynamics of dialects of modern Ukrainian language. Purpose. The purpose of the analysis is to determine the types, areal relevance and heuristic potential of phraseology of the Ukrainian resettlement dialects spread in the area between the Dniester and the Danube rivers, existing in interfering conditions, to find out some results of language contacts on this language level, preserved phrases – genetic markers and innovations, including transforms and interferems. Results. The author comes to the conclusion that transformations of genetic markers of phraseological units take place in the field of form and meaning. They lead to the emergence of new phrases, their variants, areal relevant both within the region and outside it. The process of phraseologizing, the consolidation of a certain phenomenon in phraseology, contributes to the preservation of archaic dialectal phenomena, dialectal features of maternal dialects. Originality. In contrast to the descriptive, lexicographic and linguogeographical works of previous researchers of Ukrainian dialects of this area (V. P. Drozdovsky, A. M. Mukan, A. O. Kolesnykov, the author pays separate attention to the phraseological level. Conclusion. Analysis of the phraseological level of the researched Ukrainian dialects forces us to consider the concept of phraseological unit in a broad sense. According to the study, the difference may be in the phraseological unit as a whole, as well as in its meaning, form, and in the individual components of the phraseological unit – lexemes, word forms, phrases. Prospects for further explorations are associated with detailed purposeful study of the phraseological level of these dialects through the integrated use of special program and dialect texts. It will help to clarify the existing classification of the dialect form of the national language and to improve the list of its phraseological units.